Digital Work Tools and Tasks: Firm-Level Evidence from Germany - Weller, Sabrina Inez [Verfasser]; Lukowski, Felix [Verfasser]; Baum, Myriam [Verfasser] (My University, 2020)
"The ongoing computerization of our economy is transforming the world of work. New technologies and new working requirements are leading to changes in employees' task composition. This paper analyses the influence of digital work tools on routine, manual, interactive and cognitive tasks, based on German establishment data (BIBB Establishment Panel on Training and Competence Development). A distinction is drawn between groups of employees with different skill requirements (employees performing simple, qualified and highly qualified tasks). We show that the usage rate of work tools increases with rising skill requirement level in routine, manual and non-routine tasks. Software is the most important work tool among all skill groups and tasks. Our results show that software substitutes for human labour in performing routine and manual tasks and complements for human labour in performing non-routine tasks. Work tools in the category "Measurement Devices and Diagnostic Tools" complement for human labour in performing non-routine tasks." (authors' abstract; BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; Arbeitswelt; Arbeitsmittel; Digitalisierung; Einflussfaktor; Tätigkeitsmerkmal; Routinetätigkeit; Substitution; Software